PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SDS PEMBANGUNAN BAGAN BATU - Harahap, Nuryani; ', Lazim N; Noviana, Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research up on its low usufructs student studying braze v SDS Pembangunan Baganbatu. Initially, of 24 students which reach KKM just 9 person (37,5 %). Its low causal factor result studies student because of teacher be still that more active than student tend upon learning happens. So student have no chance to develop pengetahuanya. Therefore researcher applies one kooperatif learning model type Snowball Throwing which is one model which can help student in understands learning. Type learning model Snowball Throwing giving chance to student to develop its skill. then each student makes formed question bulbous (question paper) then is thrown to other student. This research mengunakan methodics Action Research braze (PTK) with analisis's tech kualitatif's data. On action research brazes this researcher plot action with two cycles. Action performing did by acting researcher as teacher up to learning process. Activity result learns on i. cycle 62,50% by enough categories, then increasing on appointment second becomes 75,00 % get categories well. On cycle II. appointment first increases 83,33 % by good categories, then on appointment second increases again 95,83% by good peer categories. Student activity result on meet i. cycle percentage first 58,33% get enough categories, then on second appointment 70,83% also get categories well, on cycle II. first appointment 79,16% get good peer categories, on second Cycle appointment II. also experience step-up 91,66 % by ketegori tremendously good.Key Word : kooperatif' model type Snowball Throwing , IPA learned result